2011
DOI: 10.1002/jat.1779
|View full text |Cite
|
Sign up to set email alerts
|

Potential toxic effects of iron oxide nanoparticles in in vivo and in vitro experiments

Abstract: The aim of this study was to determine the potential toxic effects of iron(II,III)oxide nanoparticles (IONPs). In in vivo experiments, the toxic effects of IONPs were monitored in adult male Wistar rats by morphological methods after a single intratracheal instillation. For the control group 1 ml of physiological saline per animal was given, and the treatment group received the same volume of a suspension containing 1 and 5 mg kg⁻¹ body weight IONPs. Lungs and internal organs underwent histopathological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 33 publications
4
78
0
2
Order By: Relevance
“…Bare IONPs were found to display higher toxicity than those of both coated IONPs. In an in vivo study, Szalay et al [28] studied the toxicity of IONPs in adult male wistar rats. Pathological examination indicated a weak pulmonary fibrosis at the lungs of the exposed rat.…”
Section: Iron Oxide Nanoparticles (Ionps) and Their Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bare IONPs were found to display higher toxicity than those of both coated IONPs. In an in vivo study, Szalay et al [28] studied the toxicity of IONPs in adult male wistar rats. Pathological examination indicated a weak pulmonary fibrosis at the lungs of the exposed rat.…”
Section: Iron Oxide Nanoparticles (Ionps) and Their Toxicitymentioning
confidence: 99%
“…Pathological examination indicated a weak pulmonary fibrosis at the lungs of the exposed rat. High doses of IONPs showed higher levels of pulmonary fibrosis than lower doses [28]. Gu et al [29] demonstrated that the accumulation of IONPs was observed mainly in the liver and spleen of mice.…”
Section: Iron Oxide Nanoparticles (Ionps) and Their Toxicitymentioning
confidence: 99%
“…In adults, iron is stored in hepatocytes and tissue macrophages in response to the need for tissue storage and flows in response to the severe needs (2). Tissues can be exposed to iron and iron compounds through different ways including in hereditary diseases such as hemochromatosis or blood transfusions in lethal thalassemia and anemia, long-term hemodialysis, medical practices such as stem cell therapy, tissue engineering, or imaging (3) as well as the presence of iron particles in water, food, and air (4). Free iron, due to the oxidizing ability as well as the ability of producing oxygen radicals through Haber-Weiss reaction and also because of its strong bond with proteins, leads to iron accumulation that is cytotoxic (5).…”
Section: Introductionmentioning
confidence: 99%
“…Among the materials and technologies that have been proposed, ferromagnetic nanoparticles coupled with alternating magnetic fields (AMFs) have emerged as particularly encouraging. 12,32,38,39 Magnetic nanoparticles can be suspended in biocompatible carrier media and anatomically targeted to tumors by direct delivery via intratumor injection. 11 Magnetic materials dissipate heat from relaxation losses when they are exposed to an AMF.…”
mentioning
confidence: 99%